Penerapan Mobilisasi Dini Terhadap Penurunan Tingkat Nyeri Pada Pasien Pasca Operasi Di RS TK III Bhakti Wira Tamtama Semarang - Ainnur Rahmanti; Iqbal Wisnu P; Indri Pratiwi (Lembaga Pengembangan Kinerja Dosen, 2022)
Pain is a personal experience that is expressed differently. Medical procedures that often cause pain are surgery. Postoperative patients require maximum care to accelerate the return of body function, by providing early mobilization interventions. Early mobilization exercises can improve blood circulation which will trigger a decrease in pain. This study aims to determine the effect of early mobilization implementation on reducing pain levels in postoperative patients at Rumkit TK.III 04.06.02 Bhakti Wira Tamtama Semarang. Measurement of postoperative pain scale using Numeric Rating Scale. This study is a descriptive study with a one-case approach method. This study aims to determine the effect of early mobilization implementation on reducing pain levels in postoperative patients at Rumkit TK.III 04.06.02 Bhakti Wira Tamtama Semarang. The data collection method used is using observation sheets and early mobilization soup with inclusion criteria of 8 hours postoperative patients. The number of samples used was 2 people, the level of pain numeric rating scale 7-9 (severe pain), based on data analysis obtained the results that the level of pain of respondent I from scale 7 (severe pain) decreased to scale 5 (moderate pain), respondent I from scale 7 (severe pain) decreased to scale 5 (moderate pain) II from a scale of 7 (severe pain) decreased to 4 (mild pain). The application of early mobilization to reduce the pain scale in postoperative patients is recommended as an effective application of therapy in reducing the pain scale.